Intercultural Communication Competence Of Chinese English Majors: A Study Of Its Components And Influencing Factors In Teaching English As A Foreign Language - Liu, Han (2014)
With the rapid development of internationalization and globalization, this world is becoming smaller and smaller, and the necessity to comuunicate with people from other cultures successfully is becoming increasingly urgent. This research is designed to investigate Chinese english major's intercultural communication competence (ICC), and this target is split into following two sets of research questions.